Evaluando políticas de desarrollo humano: el caso de la agenda de política pública en el Perú - Osorio Llanos, Carmen (2010)
This article analyses the influence of the human development (HD) approachon the agenda of Peruvian politics. It examines two human developmentpolitics applied in Peru to show how the main elements of the Amartya Sen’scapacities approach can be incorporated into public policies assessment. Theanalysis shows that recognizing human agency implies a permanent dialogueamong policy makers, technicians and common citizens to set out the politicalagenda on human development. This allows them to jointly determine whatis the being and doing that society wants to prioritize; and hence, contributeto implementing more effective human development policies.